Diabetes induced internal organs inflammation in non-obese type 2 diabetic rats - Podsawee Mongkolpathumrat , Nuttikarn Nokkaew , Punyanuch Adulyaritthikul , Kantapich Kongpol , Jantira Sanit , Panyupa Pankhong , Sarawut Kumphune (Journal of Applied Pharmaceutical Science, 2019)
Diabetic complications may in part be due to inflammation. Diabetes can also develop in non-obese people. Nonetheless, organ inflammation in non-obese type 2 diabetes mellitus animals has never been investigated. The Goto- Kakizaki rats were divided into two groups: diabetes and diabetes treated with metformin. The glycemia parameters were then determined. Serum and internal organs, including the liver, kidney, and brain were collected to determine the levels of inflammatory cytokine and mRNA expression. The research found an increase in interleukin-6 (IL-6) and IL-1β cytokine levels in the liver of the diabetic group, which corresponds with the mRNA expression of both cytokines. The metformin group significantly reduces the mRNA expression of liver IL-6. In the kidney, there was an increase in IL-6 cytokine levels in the diabetic group, while the metformin group could reduce the mRNA expression level of tumor necrosis factor α (TNF-α). In addition, there were IL-6 and TNF-α cytokines level increased in the brain of the diabetic group. IL-1β mRNA expression levels increased in the diabetic group and were reduced by the metformin treatment. The metformin treatment reduced serum TNF-α cytokines. In summary, this study demonstrated that internal organ inflammation in non-obese diabetic rats, which could provide evidence for organ inflammation, may potentially explain diabetic complications.
Keywords: Diabetes, internal organs, complications, inflammation, metformin, Goto-Kakizaki rat.